Evaluation of Influencing Factors on Metabolism of Land-Based n-3 Poly Unsaturated Fatty Acids—The KoALA Study - Drobner, Timo; Braun, Theresa S.; Kiehntopf, Michael; Schlattmann, Peter; Lorkowski, Stefan; Dawczynski, Christine (Nutrients, 2023)
This study aimed to investigate the impact of influencing factors (sex, eicosapentaenoic acid (EPA) status at baseline, linoleic acid (LA) intake, milk fat intake) on the conversion of α-linolenic acid (ALA) obtained from linseed oil into its long-chain metabolites. In addition, the effect of ALA on cardiovascular risk markers was investigated. This study used a parallel design approach by randomly assigning the 134 subjects to one of four diets (high in LA (HLA); low in LA (LLA); high in milk fat (MF); control (Western diet)) each enriched with linseed oil (10 en%, 22–27 mL ≙ 13–16 g ALA). Blood samples were taken at baseline and after 4, 8, and 12 weeks of dietary intervention. The study was fully completed by 105 subjects (57.4 ± 12.1 years; 65.7% female). Results showed that ALA (296–465%), C-20:4n3 (54–140%), and EPA (37–73%) concentrations in erythrocytes increased in all groups (p < 0.01). In contrast, docosahexaenoic acid (19–35%, p < 0.01) and n-3 index (10–21%, p < 0.05) dropped in the HLA, LLA, and control groups. An increase in C-22:5n3 was only observed in the MF (36%) and control groups (11%) (p < 0.05). In addition, an increase in LA (7–27%) was found in the HLA, LLA, and control groups, whereas C-20:3n6 (16–22%), arachidonic acid (10–16%), C-22:4n6 (12–30%), and C-22:5n6 (32–47%) decreased (p < 0.01). The conversion into EPA was higher in men than in women (69 vs. 39%, p = 0.043) and in subjects with low EPA status compared to participants with high EPA status (79 vs. 29%, p < 0.001). A high LA status attenuates the conversion rate. In line with the literature, no clear effects on blood lipids and parameters of glucose metabolism were found in relation to ALA supplementation.